(untitled) (Journal of Asian Development Studies, 2024)
This study investigates the interplay between inventive passion and the effectuation process’s role in bringing product and service innovativeness. This research examines the mediating effect of effectuation in connection with the entrepreneurial inventive passion product and service innovativeness in SMEs. The study is causal and cross-sectional; SPSS version 26 is used for statistical inference, whereas Hayes macro version 4.2 is employed for regression analysis. The findings suggest that inventive passion has a significant positive relationship with product innovativeness and effectuation. Furthermore, effectuation mediates the relationship between inventive passion and product innovativeness. The study results have considerable implications for entrepreneurs and policymakers seeking to foster innovation and entrepreneurship. In a dynamic and uncertain environment, SMEs can employ compelling logic of effectuation to innovate products and services. Effectual elements provide the framework for developing the echo system for product and service inventiveness for passionate entrepreneurs which will facilitate product and service innovativeness